Hubungan Antara Pola Makan Yang Benar Dengan Gastritis Pada Mahasiswa Keperawatan Tingkat Satu Di Universitas Advent Indonesia Bandung - Tambunan, Jeremia Jonathan; Hutapea, Lyna (LPPM Institut Pendidikan Nusantara Global, 2024)
One of the diseases caused by poor diet is gastritis. Gastritis is an inflammation of the gastric mucosa which is characterized by a full stomach, pain in the pit of the stomach, nausea and vomiting. This study aims to determine the relationship between proper diet and gastritis in first-level nursing students at Bandung Adventist University. The research design used is cross sectional. Subjects who participated in this study were 63 samples selected by technique simple random sampling. The research instrument was a questionnaire to obtain data on eating patterns and the incidence of gastritis. The results of this study were that the majority of respondents had unhealthy eating patterns as many as 35 people (55.6%) and healthy eating patterns as many as 28 people (44.44%). Based on the incidence of gastritis, the majority of respondents suffering from gastritis were 60 people (95.2%) and respondents who did not suffer from gastritis were 3 people (4.8%). for analysis Chi-square obtained a value of P = 0.116 which means P>a (0.05). The conclusion of this study is that there is no relationship between proper diet and the incidence of gastritis in level 1 nursing students at the Adventist University of Indonesia.